Tuning rules for unstable dead-time processes - Rodrigues, Rejane Cavalcante Sá (2022)
Despite many advances in the field of dead-time compensators (DTCs) for unstable first-order plus dead- time (UFOPDT) processes, the tuning, in general, is manually carried out. Therefore, this paper proposes simple tuning rules for a DTC intended to UFOPDT processes. The rules are based on the relative dead time, desired closed-loop time constant, and achievable robustness. Besides, as the practical implemen- tation is always in the discrete-time domain, a method to choose the sampling period for UFOPDT pro- cesses is presented. Four simulation examples from the literature are used to show the advantages of the proposed method. In addition, an experiment with a propeller pendulum is performed to confirm such advantages in the control of a real unstable process with dead time.